Enhanced Recovery after Partial and Radical Nephrectomy Reduces Length of Stay, Opioid Use and Cost. Issue 1 (January 2020) - Swerdloff, Daniel; Podolski, Demitri; Smith, Rachel E.; Lee, Donald; Swerdloff, Michael; Feustel, Paul J.; Williams, Kanwaldeep K.; Galay, Igor; Afroze, Farzana; Kaufman, Ronald P.; Kogan, Barry A.
Abstract: Introduction: Enhanced recovery after surgery pathways are multidisciplinary, multimodal approaches to perioperative care that aim to improve patient outcomes. In this study we evaluate the outcomes of the implementation of enhanced recovery after surgery pathways in patients undergoing nephrectomy. Methods: A retrospective analysis was performed comparing patients who underwent renal surgery before vs after implementation of enhanced recovery after surgery pathways. Data analyzed included length of stay, opioid use, cost and complications before and after the enhanced recovery after surgery protocol was implemented. Results: There were 76 patients in the pre-enhanced recovery after surgery group and 42 in the enhanced recovery after surgery group. Median length of stay in the pre-enhanced vs enhanced recovery after surgery group was 3 days vs 2 days (p <0.005). For open procedures median length of stay was 5 days vs 2 days (p <0.001). For robotic procedures median length of stay decreased from 3 days to 2 days (p <0.001). Median length of stay was lower in the enhanced recovery after surgery group independent of age, sex, body mass index, American Society of Anesthesiologists® score and anesthesia time. Median total morphine equivalents decreased from 4 mg to 0 mg (p <0.005) while median total oxycodone went from 52.5 mg to 8.75 mg (p <0.005). Direct cost per patient decreased from 13, 036 pre-enhanced recovery after surgery to 9, 779 (p <0.001) in the enhanced recovery after surgery group, representing a 25% decrease. The 30-day readmission rates did not change after implementation of enhanced recovery after surgery protocol, and a National Surgical Quality Improvement Program sampling showed similar rates in complications, although this was not amenable to statistical analysis. Conclusions: Enhanced recovery after surgery improves the care of patients undergoing renal surgery. It significantly decreased length of stay, opioid use and hospital cost without having a significant effect on complications.